2004
DOI: 10.1002/art.20110
|View full text |Cite
|
Sign up to set email alerts
|

Increased prevalence of semaphorin 3C, a repellent of sympathetic nerve fibers, in the synovial tissue of patients with rheumatoid arthritis

Abstract: ObjectiveThe presence of selective sympathetic nerve repellents, i.e., semaphorins, may be responsible for the observed reduction of sympathetic innervation in the synovial tissue of patients with rheumatoid arthritis (RA). This study was undertaken to investigate the presence of different semaphorins in synovial tissue of patients with RA, patients with osteoarthritis (OA), and control subjects without inflammation.MethodsIn situ hybridizations with digoxigenin‐labeled RNA probes directed against different se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 63 publications
4
71
0
Order By: Relevance
“…13 In the present study, we also demonstrated SEMA3C in Charcot foot, which was particularly present in cells of adjacent synovial tissue and bone.…”
Section: Loss Of Sympathetic Nerves In Charcotsupporting
confidence: 78%
See 3 more Smart Citations
“…13 In the present study, we also demonstrated SEMA3C in Charcot foot, which was particularly present in cells of adjacent synovial tissue and bone.…”
Section: Loss Of Sympathetic Nerves In Charcotsupporting
confidence: 78%
“…Control stainings with preimmunization serum and with peptide-neutralized SEMA3C antibody solution were carried out in parallel. 13 These controls always yielded negative results.…”
Section: Detection Of Sema3c-positive Cellsmentioning
confidence: 98%
See 2 more Smart Citations
“…In cohort 2 only, synovial tissue samples were obtained immediately after opening the knee joint capsule, preparation of which has been described previously (20). A piece of synovial tissue of up to 9 cm 2 was dissected.…”
Section: Methodsmentioning
confidence: 99%